2008
DOI: 10.1111/j.1745-4573.2007.00101.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydrodynamic Pressure Processing and Aging on the Tenderness and Myofibrillar Proteins of Beef Strip Loins*

Abstract: This study evaluated the effects of hydrodynamic pressure (HDP) processing and aging on the tenderness and myofibrillar proteins of beef strip loins. Loins (n = 12) were halved at 48 h postmortem and assigned to HDP or control treatments. Following treatment, each half was divided into three portions for aging (0, 5 or 8 days). Samples were removed for Warner-Bratzler shear force (WBSF) determination and myofibrillar protein isolation. HDP decreased (P < 0.0001) WBSF values 23% at 0, 5 and 8 days of aging. Myo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 47 publications
4
29
0
Order By: Relevance
“…Similar results were found by Solomon et al (2006) and Bowker et al (2007Bowker et al ( , 2008, although in those studies, the authors used HDP instead of HPP for generating the pressure pulse. In spite of the differences in the processes and in the meat regarding races and sex, it is worth noting that the pulse generated by a conventional HPP system and not by an underwater explosion system such as in the HDP can lead to similar results and effects.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Similar results were found by Solomon et al (2006) and Bowker et al (2007Bowker et al ( , 2008, although in those studies, the authors used HDP instead of HPP for generating the pressure pulse. In spite of the differences in the processes and in the meat regarding races and sex, it is worth noting that the pulse generated by a conventional HPP system and not by an underwater explosion system such as in the HDP can lead to similar results and effects.…”
Section: Resultssupporting
confidence: 91%
“…In spite of the differences in the processes and in the meat regarding races and sex, it is worth noting that the pulse generated by a conventional HPP system and not by an underwater explosion system such as in the HDP can lead to similar results and effects. Solomon et al (2006) and Bowker et al (2007Bowker et al ( , 2008 reported 29 and 23 % reduction, respectively, in the shear force determined by the Warner Bratzler Shear Force Method (WBSF) in postmortem beef treated with HDP using Brahman cattle. Regardless of the maturation time, these results suggested that the HDP proved to be an effective method to increase tenderness in various meat cuts.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…All of the strip loins utilized in this study exhibited a strong aging effect with WBSF decreasing approximately 25-30% with 7 days of aging in both treated and non-treated samples. Given that the strip loins were removed from the carcasses and frozen within 48 h postmortem, prior to substantial aging tenderization, these results were not surprising and are in agreement with data showing that beef strip loins subjected to explosives-derived shockwave treatment undergo postmortem proteolysis and aging tenderization similar to non-treated controls (Bowker, Fahrenholz, Paroczay, Eastridge, & Solomon, 2008). Shockwaves generated by explosives have demonstrated the ability to enhance both the rate and extent of postmortem aging tenderization .…”
Section: Discussionsupporting
confidence: 79%
“…Tenderisation during aging has been mainly ascribed to the proteolytic decomposition of myofibrillar proteins, titin, nebulin, troponin-T, desmin, and filamin (Huff-Lonergan et al 1996), while the most prominent breakdown product is derived from troponin-T (Bowker et al 2008;Chen et al 2011). The presence of a 30 kDa fragment of troponin-T has been found in aged beef (Ho et al 1996), chicken (Mikami et al 1987), pork (Lametsch et al 2002), and lamb (Kuber et al 2003).…”
mentioning
confidence: 97%